Time‐selective integrated scheduling algorithm with backtracking adaptation strategy. Issue 3 (5th July 2018) - Zhang, Xiaohuan; Xie, Zhiqiang; Xin, Yu; Yang, Jing
Abstract: Currently, integrated scheduling algorithms schedule processes using fixed rules, making it difficult to balance serial and parallel processes in product craftsmanship trees while conducting complicated single product scheduling. To solve this problem, we propose a time‐selective integrated scheduling algorithm with a backtracking adaptation (TISAWBA) strategy. The proposed process sequence sorting strategy aims to determine process scheduling sequences based on the overall structure of the machining craftsmanship tree. The proposed time‐selective scheduling strategy aims to select the process portfolio with the minimum total elapsed time for machining from a process portfolio set based on craftsmanship tree structure. The proposed backtracking adaptation strategy conducts backtracking adaptation to find process portfolios having a total elapsed machining time greater than the "scheduling reference time." Finally, illustrative use cases verify that TISAWBA guarantees parallel processing for parallel processes and elevates the proximity of serial processes, generating optimized integrated scheduling results.